Implementasi Model Project-Based Learning Berbantuan Simplebooklet dan Canva pada Pembelajaran IPS Kelas VI SDN 1 Bangoan - Ning Wahyuni; Sulastri Rini Rindrayani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This conceptual study examines the implementation of the Project-Based Learning (PBL) model, supported by digital media tools such as Simplebooklet and Canva, in Social Studies learning for sixth-grade students at SDN 1 Bangoan. The study arises from the need for contextual, engaging, and student-centred learning as a response to the typically theoretical and less interactive nature of Social Studies instruction. Through the integration of digital media, students can engage in meaningful projects that foster critical thinking, collaboration, creativity, and digital literacy. The learning process includes stages such as problem formulation, project planning, product development, and reflection. This study presents a conceptual overview showing that implementing the PjBL model with the support of Simplebooklet and Canva can enhance student engagement and strengthen understanding of the subject matter.